Programa PDI en el desarrollo de la competencia “Explica el mundo físico” en estudiantes de educación primaria - Trujillo, 2019 - Cedano Trujillo, Elizabet (2019)
This study was carried out with the purpose of determining to which extent the application of the PDI Program, based on the use of an interactive digital whiteboard, improves the skill “Explain the physical world based on knowledge of living organisms, matter, energy, biodiversity, earth and universe”, with sixth grade students of educational institution Nº. 81017 Santa Edelmira, the sample of the study consisted of 49 sixth grade students, 26 the experimental group and 23 the control group, it was used at which were applied a science and technology test, which was made up of 14 items with a maximum score of 28 points. After the application of the program, there was a significant development of the competence in the students of experimental group, as evidenced in the results of non-parametric Mann Whitney U test with an average range of 36.19, being almost three times its value is greater than that of the control group (12, 35) and a p-value of 0.000, which is less than the alpha value (0,05), corroborating the significant results of the application of the program.